Competition, Predation & Mutualism - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2021)
Associate Professor Dr. Asmida Ismail was invited as a guest lecturer in a virtual event organised by Sepuluh Nopember Institute of Technology (ITS) on 15 June 2021. The theme of the talk Predation & Mutualism". was "Competition.